Study on a 3D-Bioprinted Tissue Model of Self-Assembled Nanopeptide Hydrogels Combined With Adipose-Derived Mesenchymal Stem Cells - Zhou, Guanzhou; Tian, Ailing; Yi, Xin; Fan, Lufeng; Shao, Wenchong; Wu, Han; Sun, Nianfeng (Frontiers in Bioengineering and Biotechnology, 2021)
Objective: This study aimed to observe the cell growth status and multidirectional differentiation ability in a 3D-bioprinted tissue model of self-assembled nanopeptides and human adipose-derived mesenchymal stem cells (Ad-MSCs). Methods: Primary Ad-MSCs were isolated, cultured, and identified by flow cytometry. Tissue models were printed via 3D bioprinting technology using a “biological ink” consisting of a mixed solution of self-assembled nanopeptides and Ad-MSCs. Ad-MSCs were induced into osteogenic, adipogenic, and endothelial differentiation and compared with the control groups by staining. Results: The nanopeptide fiber was 10–30 nm in diameter and 200–500 nm in length under the atomic-force microscope. It had the characteristics of nano-scale materials. Flow cytometry showed that the isolated and cultured cells were positive for CD29 (98.51%), CD90 (97.87%), and CD166 (98.32%) but did not express CD31 (1.58%), CD34 (2.42%), CD45 (2.95%), or human leukocyte antigen (HLA)-DR (0.53%), consistent with the immunophenotype of Ad-MSCs. Then, a tissue model was printed using the biological ink, followed by induction of differentiation of Ad-MSCs within the tissue model. Alizarin red S staining showed the formation of calcium nodules in the osteogenesis induction experimental group, and oil red O stained lipid droplets in Ad-MSCs in the adipogenesis induction experimental group, whereas the two control groups were not stained. Conclusion: Ad-MSCs from primary cultures have the characteristics of stem cells. Self-assembled nanopeptide hydrogel is a good tissue engineering material that can serve as an extracellular matrix. Ad-MSCs in the 3D-printed tissue model using a biological ink consisting of a mixed solution of self-assembled nanopeptides and Ad-MSCs grew well and still had strong differentiation ability.